Quality Control Analysis Using Flowchart, Check Sheet, P-Chart, Pareto Diagram and Fishbone Diagram - Khairun Nadiyah; Grita Supriyanto Dewi (OPSI, 2022)
SP Aluminum is engaged in the manufacturing industry by producing cooking utensils. In its application, SP Aluminum has tried to produce quality products to satisfy consumers. However, there are still defects that appear in its products. Another problem is the product defects have not been handled seriously by the company. Based on these problems, this study utilizes 5 quality control methods from seven tools: flowchart, check sheets, p-chart, Pareto diagram, and fishbone diagrams. This research is a quantitative qualitative with direct data collection through observation and interviews. The data taken is the product defect in Super Wok Number 12. There are 49 defects data that have been processed. From the results of the check sheet analysis, it was found that the intensity category of the product defects occurrence was obtained. Furthermore, control chart analysis show that there are some data that are out of control. Then, Pareto diagram analysis show the most dominant types of defects are holes, dregs, and pores. Finally, the factors of the absence of written SOPs, less thorough and less competent employees, poor working environment, lack of machine maintenance, poor handling of raw materials and inappropriate material handling processes were common causes of product defects.